Considering change with archaeological data: Reevaluating local variation in the role of the 4.2k BP event in Northwest China. (February 2021) - Jaffe, Yitzchak Y; Hein, Anke
Over the past two decades, environmental studies in research on prehistoric China have been gaining popularity and importance. For Northwest China in particular, climate change, especially the so-called 4.2k BP event has been seen as the main reason for an alleged collapse of Late Neolithic societies and a transition to pastoral-heavy economies and mobile lifeways. Yet, these explanatory models tend to rely on limited archaeological and environmental data and non-contemporaneous historical data, resulting in simplistic causal relationships between environmental changes and social response. This paper re-evaluates the Incipient Bronze Age in China's Northwestern region, discussing evidence for climate change and its exact dates, as well as textual and archaeological evidence. We argue that the old narratives perpetuating the image of a dichotomy between Steppe and Sown are inaccurate, while large-scale models of region-wide subsistence change in response to climate cooling tend to disregard local developments and group-specific responses as well as chronological issues. Focusing on the Xindian and Siwa archaeological phenomena, this paper provides a view into sub-regional responses to this climate event, warning against simplistic broad-brush reconstructions and calling for both a return to archaeological fundamentals and large-scale intensive fieldwork and interdisciplinary studies involving archaeologists, paleobotanists, zooarchaeologists, isotope specialists, and climate scientists.